Disclosure Overload? A Professional User Perspective on the Usefulness of General Purpose Financial Statements - Drake, Michael S.; Hales, Jeffrey; Rees, Lynn (Contemporary Accounting Research, 2019)
ABSTRACT We survey a broad group of professionals who use financial statements as part of their job to assess the extent to which they believe financial reports suffer from disclosure overload. Consistent with the claims made by regulators, auditors, and preparers, we find that a significant portion of professional financial statement users believe disclosure overload is a problem. However, this group is in the minority, with about twice as many professional users believing that overload is not a problem and that more information should be disclosed in financial statements. This dichotomy presents a difficult challenge to standard setters aiming to improve financial reporting by altering the amount of information provided in financial reports. To that end, we complement existing research on the informativeness of accounting information by measuring perceptions of the usefulness of the various financial statements and their footnotes across a variety of tasks. Finally, we develop a framework that could be useful in developing a theory of disclosure overload.